Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1515/jpem.1996.9.5.511
|View full text |Cite
|
Sign up to set email alerts
|

Final Height Outcome in Both Untreated and Testosteronetreated Boys with Constitutional Delay of Growth and Puberty

Abstract: The present retrospective study is based on a historical follow-up of 49 boys with constitutional delay of growth and puberty (CDGP) who went into puberty spontaneously (27 cases) or induced by depotestosterone treatment, 50 mg/ month for 6 months (22 cases). At the time of puberty the two groups of boys were similar in bone age, height deficiency, target height (TH) and had similar predicted final heights (FH). Their FH was measured and compared with TH calculated from measured parents' heights. FH did not si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…Subjects with CDGP have previously been shown to achieve FH that is normal or lower-range normal compared with the general population, with values ranging from –1.9 to –0.6 SDs [5,6,7,8,9,10, 12]. However, not all boys with CDGP reach their genetic TH [7, 9, 10, 13].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Subjects with CDGP have previously been shown to achieve FH that is normal or lower-range normal compared with the general population, with values ranging from –1.9 to –0.6 SDs [5,6,7,8,9,10, 12]. However, not all boys with CDGP reach their genetic TH [7, 9, 10, 13].…”
Section: Discussionmentioning
confidence: 99%
“…However, not all boys with CDGP reach their genetic TH [7, 9, 10, 13]. Although in some previous studies FH of CDGP cases was only 0.1–0.2 SDs smaller than their TH [5, 8], several other studies have reported FH from 0.8 to 1.5 SDs below TH [7, 8,10,11,12,13]. According to one study, 58% of cases with CDGP did not exploit their full genetic height potential [13].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations